Words going around the world: the personalization of disasters by the media - Franz Amaral, Márcia (2016)
This article analyzes the role of journalistic testimony in the case of news coverage of disasters, describes some frequently narrative settings and explores the details surrounding its presentation in the media. From a theoretical reflection on testimonies in journalism, we studied particularly illustrative cases concerning two disasters: the eruption of volcano Nevado del Ruiz (1985) in Colombia and the rupture of a tailings dam in Brazil, 30 years later. We conclude media testimonies are arranged by the journalistic narrative, which could both restrict them to their uniqueness as much as expand them along with a contextualization of the disaster.